SAVI: molecular mechanisms, clinical spectrum and precision medicine approaches beyond type-I IFN - Michele Manganelli; Paola Cantalice; Jona Papri; Enrico Drago; Nicole De Lucchi; Giulia Accorsi; Chiara Fresia; Simonetta Simonetti; Gabriella Guida; Gerardo Cazzato; Mario Della Mura; Giuseppe Ingravallo; et al. (Frontiers in Immunology, 2026)
Type I interferonopathies (TI-IFN) represent a heterogeneous group of autoinflammatory disorders characterized by upregulated type I interferon (IFN) signaling. Among them, STING-associated vasculopathy with onset in infancy (SAVI) is a rare, severe autoinflammatory disease caused by gain-of-function mutations in the STING1 gene. Mechanistically, these mutations lead to a constitutive activation of the STING protein, resulting in excessive type I interferon production, which drives chronic inflammation and damage to various organs, primarily as cutaneous vasculopathy and progressive interstitial lung disease (ILD). Emerging clinical data indicate that current therapeutic options – including Janus kinase inhibitors (JAKi), biological agents as anifrolumab and solid organ transplantation – for SAVI face limited and often inconsistent long-term efficacy, highlighting a significant unmet need. Consistently, preclinical models highlight that SAVI pathogenesis is not only driven by the interferon storm, but relies also on non-canonical IFN-independent cellular pathways across distinct hematopoietic and non-hematopoietic compartments. This review provides a comprehensive overview of SAVI pathogenesis, from mutational mechanisms and comparative phenotypes to the clinical challenges of advanced interventions. Finally, we discuss future therapeutic prospects and clinical implications, exploring next-generation frontiers such as patient-derived induced pluripotent stem cell (iPSCs) models, hematopoietic stem cell transplantation (allo-HSCT) and gene editing (GE) technologies. The transition from immune - to a mutational-perspective, provides a foundational framework to optimize diagnostic and therapeutic strategies for precision medicine in SAVI patients.